Diversity of mariner-like elements in Orthoptera - K. Ustyantsev; M. Biryukov; I. Sukhikh; N. V. Shatskaya; V. Fet; A. Blinov; I. Konopatskaia (Вавиловский журнал генетики и селекции)
Mariner-like elements (MLEs) are among the most widespread DNA transposable elements in eukaryotes. Insects were the first organisms in which MLEs were identified, however the diversity of MLEs in the insect order Orthoptera has not yet been addressed. In the present study, we explore the diversity of MLEs elements in 16 species of Orthoptera belonging to three infraorders, Acridoidea (Caelifera), Grylloidea (Ensifera), and Tettigoniidea (Ensifera) by combining data mined from computational analysis of sequenced degenerative PCR MLE amplicons and available Orthoptera genomic scaffolds. In total, 75 MLE lineages (Ortmar) were identified in all the studied genomes. Automatic phylogeny-based classification suggested that the current known variability of MLEs can be assigned to seven statistically well-supported phylogenetic clusters (I–VII), and the identified Orthoptera lineages were distributed among all of them. The majority of the lineages (36 out of 75) belong to cluster I; 20 belong to cluster VI; and seven, six, four, one and one lineages belong to clusters II, IV, VII, III, and V, respectively. Two of the clusters (II and IV) were composed of a single Orthoptera MLE lineage each (Ortmar37 and Ortmar45, respectively) which were distributed in the vast majority of the studied Orthoptera genomes. Finally, for 16 Orthoptera MLE lineages, horizontal transfer from the distantly related taxa belonging to other insect orders may have occurred. We believe that our study can serve as a basis for future researches on the diversity, distribution, and evolution of MLEs in species of other taxa that are still lacking the sequenced genomes.